The complete chloroplast genome sequence of Euphorbia lathyris L. (Euphorbiaceae) - Ma, Wenqi (Mitochondrial DNA B Resour, 2020)
Euphorbia lathyris L. is a well-known bioenergy plant cultivated in many parts of the world. In this study, we sequenced the complete chloroplast (cp) genome sequence of E. lathyris to investigate its phylogenetic relationship in the family Euphorbiaceae. The cp genome was 163,738 bp in length, consisting of a pair of inverted repeats (IRa and IRb: 26,837 bp) separated by a large single-copy region (LSC: 91,783 bp) and a small single-copy region (SSC: 18,281 bp). The GC content of whole cp genome is 35.6%. Annotation showed the presence of 113 unique genes with 79 protein-coding genes, four tRNA genes, and 30 rRNA genes. Phylogenetic analysis indicated that E. lathyris was in the basal position of subgen. Esula, closely related to sect. Esula and sect. Helioscopiae.